Socio Economic Profile of Goat Farmers in Kallakurichi District of Tamil Nadu, India - , A. Rajadurai; , A. Elango; , Periyasamy Vijayakumar; , P. Senthilkumar; , K.R. Pushpanathan; , K. Rajendran; , Arumugam Sakthivel Selvan; , Ramalingam Suresh; , P. Veeramani (Archives of Current Research International, 2025)
The present study aims to analyze the socio-economic profile of goat farmers in the Kallakurichi district of Tamil Nadu, a region where livestock rearing plays a pivotal role in rural livelihoods. Goat farming served as a significant regular source of income and employment for small and marginal farmers, particularly in economically weaker sections. A stratified random sampling method was employed to select goat farmers from various blocks of the district. Primary data were collected through structured interviews and questionnaires. Survey data was collected from 240 progressive goat farmers in the study area with a pre-tested questionnaire by personal interview. The statistically analysed data revealed that the majority of the goat farmers in Kallakurichi District were women (76.7 %), old aged (52.5 %) and illiterate (63.4 %) owning an average flock size of 48 numbers of goats (64.1 %) and the majority are small farmers (61.6 %) holding less than 2.5 acres of agricultural land. The major primary occupation of the respondents was goat farming having experience of 16.39 years. These findings reveal that most goat farmers are smallholders with limited education and land resources, relying heavily on goat rearing as a supplementary source of income for poor. Women participation in goat farming is notably high, reflecting the gendered nature of livestock management in the Kallakurichi district. The study underscores the need for targeted policy interventions, capacity-building programs, and improved access to credit and veterinary care to enhance the livelihoods of goat farmers in the Kallakurichi district.